Is training policy for general practitioners in China charting the right path forward? a mixed methods analysis - Shi, Jianwei (BMJ Open, 2020)
OBJECTIVES: Since 2010, the Chinese government has gradually increased its investment in the training of general practitioners (GPs) to support their role as ‘gatekeepers’ in the healthcare system. However, this training is still organised from the perspective of specialist care. We aimed to assess the appropriateness of the principal GP admission training programme curricula in China, including Residents Training for GPs (RTGP), Residents Training for Assistant GPs (RTAGP) and Training for Specialists with General Practice interest (TSGP). SETTING: The study focussed on GP training programmes in Shanghai, China. PARTICIPANTS: Data on disease competences developed in three GP clinical training programmes (RTGP, RTAGP and TSGP) were derived from official programme training manuals. Data on the proportion of outpatient visits for each disease were taken from the Shanghai community healthcare centres grassroots outpatient database. PRIMARY AND SECONDARY OUTCOME MEASURES: We first conducted a quantitative analysis by comparing the structure of current training curricula with actual outpatient utilisation patterns across all community healthcare institutions in Shanghai from 2014 to 2018. Qualitative analysis was then conducted to evaluate GP training programmes based on Donabedian’s model. RESULTS: Quantitative analysis showed that the distribution of diseases for which competences were taught did not match the composition of outpatient visits in community healthcare institutions. Concerns identified through qualitative analysis included teachers who were mostly specialists, lack of equipment for differential diagnosis in community healthcare institutions, insufficient teaching of referral standards and GP training in large hospitals that consistently neglected communication skills. CONCLUSIONS: The establishment and implementation of admission training programmes for GPs in China lacks a focus on general practice training and may be improved by adopting an evidence-based general perspective aligned with the medical needs of the community.